An Experience with Management of Hemoperitoneum in Blunt Injury of Abdomen at Tertiary Care Center of Western Nepal - Mishra, Santosh; Chandra, Kailash; Paudel, Kumar (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Blunt abdominal trauma results in huge burden of morbidity and mortality among all age groups caused mainly by road traffic accident, fall from height and physical assault. This study was designed to evaluate the outcome of management of hemoperitoneum in blunt injury of abdomen. MATERIAL AND METHODS: This is a prospective observational study involving 100 cases of blunt abdominal injury during the period from 1st December, 2014 to 13th March 2016 in UCMS-TH, Bhairahawa, Nepal. Documentation of the patients which included identification, history, clinical findings, diagnostic tests, operative findings, operative procedures, complications during hospital-stay was done. The decision regarding operative or non- operative management was made by specialist surgeon. RESULTS: The majority of the patients belonged to 21- 30 years age group. 72 cases were male while 28 were female. 93 patients were managed conservatively while 7 patients were operated. Most common mode of injury was road traffic accident (RTA) (74%) followed by fall form height (20%). Most common organ to be injured was spleen (65%) followed by liver (26%). 93 % patients underwent non-operative management while 7 % were operated. Mortality rate was 0% among the non- operative and 14.29% in operative cases. CONCLUSION: Non operative management in patient with hemoperitoneum with regular monitoring of vitals and repeated clinical assessment can reduce the operative need , morbidity and length of hospital stay. Non-operative Management (NOM) for blunt abdominal injuries was found to be highly successful in 93% of the patients in this study.